2020
DOI: 10.7554/elife.61591
|View full text |Cite
|
Sign up to set email alerts
|

Precisely timed dopamine signals establish distinct kinematic representations of skilled movements

Abstract: Brain dopamine is critical for normal motor control, as evidenced by its importance in Parkinson Disease and related disorders. Current hypotheses are that dopamine influences motor control by 'invigorating' movements and regulating motor learning. Most evidence for these aspects of dopamine function comes from simple tasks (e.g., lever pressing). Therefore, the influence of dopamine on motor skills requiring multi-joint coordination is unknown. To determine the effects of precisely-timed dopamine manipulation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 79 publications
5
35
0
Order By: Relevance
“…Notably, both optogenetic inhibition and stimulation of substantia nigra pars compacta dopamine cells or D1-expressing MSNs have been shown to disrupt ongoing movements (Bova et al, 2020;Tecuapetla, Jin, Lima, & Costa, 2016), which parallels the effect observed here that systemic administration of not just the D1R antagonist but also the D1R agonist slowed travel to the lever. The latter manipulation also caused a small but reliable increase in incorrect lever presses on Go trials, and both effects may reflect competition between different potential reward-associated instrumental responses in dorsal striatum (Bova et al, 2020).…”
Section: Discussionsupporting
confidence: 76%
“…Notably, both optogenetic inhibition and stimulation of substantia nigra pars compacta dopamine cells or D1-expressing MSNs have been shown to disrupt ongoing movements (Bova et al, 2020;Tecuapetla, Jin, Lima, & Costa, 2016), which parallels the effect observed here that systemic administration of not just the D1R antagonist but also the D1R agonist slowed travel to the lever. The latter manipulation also caused a small but reliable increase in incorrect lever presses on Go trials, and both effects may reflect competition between different potential reward-associated instrumental responses in dorsal striatum (Bova et al, 2020).…”
Section: Discussionsupporting
confidence: 76%
“…The possible neural substrates for such variability are broad. One candidate is differences in dopamine signaling/receptor profiles, as dopamine plays an important role in motor adaptation ( Panigrahi et al, 2015 ; Bova et al, 2020 ). Other possibilities include differences in cortical plasticity ( Li et al, 2017 ; Hyland et al, 2019 ) and corticostriatal coherence ( Lemke et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, coordinated corticostriatal activity could be correlated with changes in fine digit kinematics not evident from success rate. Indeed, previous work found that optogenetic manipulations of substantia nigra pars compacta dopamine neurons during skilled reaching disrupted the coordinated execution of digit movements with gross forelimb movements ( Bova et al, 2020 ). Therefore, basal ganglia circuitry does regulate some aspects of fine digit control, or at least its timing with respect to gross forelimb movements.…”
Section: Discussionmentioning
confidence: 99%
“…After rats completed training, we implanted an optical fiber over SNc contralateral to the rat's preferred reaching paw. Opsin expression was restricted to TH-expressing neurons in SNc projecting to striatum, and nigrostriatal TH expression was preserved (Figure S1, Bova et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to differences in AIMs between ''reaching'' and ''non-reaching'' epochs, ''non-reaching'' AIMs were more severe with inter-reach than during-reach stimulation (Figure 3D). This is despite the fact that the duration of stimulation was similar for both groups, with a median during-reach stimulation duration of 5.37 s and a median inter-reach stimulation duration of 5 s (Bova et al, 2020). This suggests two (D) A single skilled reaching trial.…”
Section: Aim Intensity Is Influenced By Behavioral Contextmentioning
confidence: 96%